2007
DOI: 10.1038/oby.2007.305
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐Adipocyte Interaction: Marked Interleukin‐6 Production by Lipopolysaccharide

Abstract: Objective: Recent studies suggested macrophages were integrated in adipose tissues, interacting with adipocytes, thereby exacerbating inflammatory responses. Persistent low-grade infection by gram-negative bacteria appears to promote atherogenesis. We hypothesized a ligand for tolllike receptor 4 (TLR4), bacterial lipopolysaccharide (LPS), would further exaggerate macrophage-adipocyte interaction. Research Methods and Procedures: RAW264.7 macrophage cell line and differentiated 3T3-L1 preadipocytes were co-cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 12 publications
(14 reference statements)
3
55
0
1
Order By: Relevance
“…We suggested in our previous study that TNF-a secreted from RAW macrophages plays important roles in markedly upregulating IL-6 translation in 3T3-L1 adipocytes, as the neutralizing TNF-a action with antibodies partially abolished the enhanced IL-6 production. 9 Therefore, we speculate that, at least in this situation, these RAW macrophages have the M1 phenotype. In fact, it has already been demonstrated that NF-kB is activated, and that cyclooxygenase-II, TNF-a, inducible nitric oxide synthase and IL-12 are expressed in response to LPS in RAW macrophages.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…We suggested in our previous study that TNF-a secreted from RAW macrophages plays important roles in markedly upregulating IL-6 translation in 3T3-L1 adipocytes, as the neutralizing TNF-a action with antibodies partially abolished the enhanced IL-6 production. 9 Therefore, we speculate that, at least in this situation, these RAW macrophages have the M1 phenotype. In fact, it has already been demonstrated that NF-kB is activated, and that cyclooxygenase-II, TNF-a, inducible nitric oxide synthase and IL-12 are expressed in response to LPS in RAW macrophages.…”
Section: Discussionmentioning
confidence: 83%
“…8 We previously reported that co-culturing adipocytes and macrophages in the presence of endotoxin resulted in markedly enhanced (more than 100-fold increase) production of IL-6 as compared with culturing each cell type alone, and suggested that co-existence of adipocytes and macrophages in the presence of TLR-4 ligands further exacerbates obesity-associated inflammatory conditions. 9 These data also suggest that gene expressions other than that of IL-6 may also be greatly influenced, in adipocytes co-cultured with macrophages, by the presence of TLR-4 ligand. Therefore, in this study, we analyzed gene expression profiles in adipocytes co-cultured with macrophages in the presence of endotoxin and attempted to detect genes with differential expressions under such conditions to further understand dynamic changes in gene expressions in adipocytes.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Also, the duration of coculture influences the increase in TNF-␣ mRNA expression in cocultures of 3T3-L1 and THP-1 (31). Incubation with bacterial lipopolysaccharide in a coculture of 3T3-L1 and RAW264 did not influence TNF-␣ production but increased IL-6 production 100-fold, suggesting an exaggerated biological interaction between macrophages and adipocytes in persistent low-grade infection by gram-negative bacteria (35).…”
Section: Discussionmentioning
confidence: 96%